Genetics of clusterin isoform expression and Alzheimer's disease risk. - I-Fang Ling (Public Library of Science (PLoS), 2012)
The minor allele of rs11136000 within CLU is strongly associated with reduced Alzheimer's disease (AD) risk. The mechanism underlying this association is unclear. Here, we report that CLU1 and CLU2 are the two primary CLU isoforms in human brain; CLU1 and CLU2 share exons 2-9 but differ in exon 1 and proximal promoters. The expression of both CLU1 and CLU2 was increased in individuals with significant AD neuropathology. However, only CLU1 was associated with the rs11136000 genotype, with the minor "protective" rs11136000T allele being associated with increased CLU1 expression. Since CLU1 and CLU2 are predicted to encode intracellular and secreted proteins, respectively, we compared their expression; for both CLU1 and CLU2 transfected cells, clusterin is present in the secretory pathway, accumulates in the extracellular media, and is similar in size to clusterin in human brain. Overall, we interpret these results as indicating that the AD-protective minor rs11136000T allele is associated with increased CLU1 expression. Since CLU1 and CLU2 appear to produce similar proteins and are increased in AD, the AD-protection afforded by the rs11136000T allele may reflect increased soluble clusterin throughout life.